Strategies for expanding colorectal cancer screening at community health centers. (1st July 2013) - Sarfaty, Mona; Doroshenk, Mary; Hotz, James; Brooks, Durado; Hayashi, Seiji; Davis, Terry C.; Joseph, Djenaba; Stevens, David; Weaver, Donald L.; Potter, Michael B.; Wender, Richard
<x xml:space="preserve">Abstract</x> Community health centers are uniquely positioned to address disparities in colorectal cancer (CRC) screening as they have addressed other disparities. In 2012, the federal Health Resources and Services Administration, which is the funding agency for the health center program, added a requirement that health centers report CRC screening rates as a standard performance measure. These annually reported, publically available data are a major strategic opportunity to improve screening rates for CRC. The Patient Protection and Affordable Care Act enacted provisions to expand the capacity of the federal health center program. The recent report of the Institute of Medicine on integrating public health and primary care included an entire section devoted to CRC screening as a target for joint work. These developments make this the ideal time to integrate lifesaving CRC screening into the preventive care already offered by health centers. This article offers 5 strategies that address the challenges health centers face in increasing CRC screening rates. The first 2 strategies focus on improving the processes of primary care. The third emphasizes working productively with other medical providers and institutions. The fourth strategy is about aligning leadership. The final strategy is focused on using tools that have been derived from models that work. CA Cancer J Clin 2013;63:221–231. ©2013 American Cancer Society, Inc.